PENGARUH RETURN ON EQUITY (ROE), EARNING PER SHARE (EPS), DEBT TO EQUITY RATIO (DER), DAN KEBIJAKAN DIVIDEN TERHADAP NILAI PERUSAHAAN (Pada Perusahaan Sektor Pertambangan Batubara Yang Terdaftar Di BEI Tahun 2014-2016) - Lukluatul Fadillah; Ronny Malavia Mardani; Budi Wahono (UNIVERSITAS ISLAM MALANG, 2019)
ABSTRACTThe purpose of this study was to determine the effect of Returm On Equity (ROE), Earning Per Share (EPS), Debt to Equity Ratio (DER) and Dividend Policy on firm value in coal mining companies. The population in this study were 22 coal mining companies listed on the Stock Exchange. And the purposive sampling method as a method in sampling, so that 10 companies were obtained as samples. The analytical method used is multiple linear analysis to determine the x variable against y. From the analysis of the data obtained the results of the study that the Return On Equity (ROE) has no significant negative effect on firm value, Earning Per Share (EPS) has a significant positive effect on firm value, Debt to Equity Ratio (DER) has no significant negative effect on firm value and dividend policy dividend policy variables do not produce test output because many companies do not distribute dividends so that when data is detected by outliers, all dividend data included in the outlier category is 0. So the variable dividend policy cannot be tested.Keywords: Return On Equity (ROE), Earning Per Share (EPS), Debt to Equity Ratio (DER), Dividend Policy and the firm value.